Nematocarcinus Milne Edwards, 1881 (Crustacea, Decapoda) from Southwestern Atlantic, including the Southern Mid-Atlantic Ridge area - Cardoso, Irene A.; Burukovsky, Rudolf N. (Zootaxa, 2014)
The deep sea shrimp genus Nematocarcinus Milne Edwards, 1881 includes 47 species, ten of them have been recorded from the Atlantic Ocean. Herein, material sampled during three scientific projects (REVIZEE Central Fishery project; Campos Basin Deep Sea Environmental Project; Evaluation of Environmental Heterogeneity in the Campos Basin) made in the Southwestern Atlantic, off Brazil, is examined. In addition, material sampled from the South Mid Atlantic Ridge (MAR-ECO Project) was also examined. Four species are recorded for the first time to the southwestern Atlantic Ocean including Mid Atlantic Ridge area: Nematocarcinus faxoni Burukovsky, 2001; N. gracilipes Filhol, 1884; N. rotundus Crosnier & Forest, 1973 and N. tenuipes Spence-Bate, 1888.